Secondhand smoke in the densely populated urban setting: A cross‐sectional survey of exposure, knowledge, attitudes, and respiratory symptoms. (28th June 2022) - Boey, Clement Peng Hee; Quaye, Sharon Esi Duoduwa; Cook, Alex R.; Seow, Wei Jie; van der Eijk, Yvette
Abstract: Secondhand smoke (SHS) remains a common health threat in densely populated, urban settings. We estimated the prevalence of exposure and associated respiratory symptoms, knowledge, attitudes, and behaviors in a multi‐ethnic, weighted sample of Singapore residents using a cross‐sectional survey of 1806 adults. We weighted data to match the national population in terms of gender, ethnicity, and education level and analyzed data using descriptive statistics, bivariate analyses, multiple linear and logistic regressions, and a multinomial logistic regression model. About 88% of respondents reported regular SHS exposure. Nearly 57% reported exposure to neighbors' SHS at home. Respiratory symptoms were reported by 32.5% and significantly associated with exposure to daily (AOR = 2.63, 95% CI = 1.62–4.36), non‐daily (AOR = 1.75, 95% CI = 1.14–2.77), and neighbors' (AOR = 1.37, 95% CI = 1.07–1.76) SHS. More knowledge of SHS was associated with male gender ( β = 0.28, p = 0.0009) and higher household income (linear trend; p = 0.0400). More negative attitudes to SHS were associated with older age (linear trend; p < 0.0001). Engaging in behaviors to avoid SHS was associated with a more negative attitude to SHS (AOR = 1.09–1.23). SHS exposure is common in Singapore's densely populated setting and associated with respiratory symptoms, even if exposure is non‐daily or from neighboring homes.